Pengaruh Metode Sugesti Imajinasi Melalui Media Musik Instrumental Terhadap Keterampilan Menulis Puisi Siswa Kelas XI SMA Negeri 1 Cihara - Yolanda, Yolanda (Universitas Mathla'ul Anwar Banten, 2024)
Imagination suggestion method through instrumental music media on the poetry writing skills of class XI high school students. Difficulty in thinking creatively in high school students is characterized by students having diffuculty working on questions that are different from those given by their teachers. This research aims to determine the difference in the influence of the writing skills of students who learn using the imagination suggestion method and students who use the literacy learning method. The method in this research uses quantitative methods. The population and sample in this study were class XI students of SMA Negeri 1 Cihara in 2 classes seleced at random or random sampling, The isntrument used in this research was a poetry writing skills test. The test used is a question type test. Based on the results of data analysis from this research, the conclusions were obtatiend: There is a difference in the influence of the poetry writing skills of students who learn using the imagination suggestion method and students who learn using the literacy method. The poetry writing skills of students who learn the imaginave suggestion method are better than students who learn using the literacy method. This can be seen from the results of the hypotesis test, namely by using the Mann-Whitnney Test from the results of the gain score data, that the results obtained are an Asymp Sig value of 0,005 < 0,05, meaning that H0 is rejected and H1 is accepted. So it can be stated that there is a significant difference in the influence of the imaginative suggestion method through instrumental music on the poetry writing skills of high school students. Keywords: Poetry writing skills, imagination suggestion method.